Morphological evolution studies of pitting corrosion of Stainless Steel - Gualteros Vanegas, Mayra Liliana (Curtin University, 2024)
A novel method was developed to explore and analyse the morphology of singular pits. Subsequently, this sample configuration was utilized in ex-situ and in-situ examinations to assess the influence of current and potential on the pit geometry development in 316L-SS foils. Following this, the study investigated the effect of sample orientation on pit growth morphology and examined the impact of decreased galvanostatic current on pit morphology transition. Finally, the study explored the influence of applied stress on pit morphology.